4 - Institutional Constraints Affecting Quality Assurance Processes in Tanzania’s Private Universities - Ishengoma, Johnson Muchunguzi; Mgaiwa, Samson John (Journal of Higher Education in Africa, 2022)
The purpose of this study is to identify the institutional constraints of quality assurance processes in Tanzania’s private universities and colleges. The descriptive survey design combines qualitative and quantitative research approaches. Purposive, stratified, and random sampling procedures are used to select a sample of 486 participants in the study who comprised 191 academic staff, 291 students, and 4 quality assurance officials from four private universities. Questionnaires and interviews are used for data collection. The findings indicate that inadequate financing, lack of capacity in terms of adequate, qualified and experienced human resources to undertake quality assurance functions, lack of clear and viable quality assurance policies, lack of awareness on quality assurance issues, and lack of academic leadership were the identified major institutional constraints to quality assurance processes in Tanzania’s private universities. The theoretical and policy implications of these findings are also discussed.